2015
DOI: 10.7727/wimjopen.2014.220
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Parapelvic Cyst by Internal Drainage Technology Using Ureteroscope and Holmium Laser

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…have reported to use a rollerball electrode to treat renal cyst by inspecting and cauterizing the inter cyst surface through a 26Fr percutaneous channel; this method has been shown to be a safe, minimally invasive, and effective technique for the management of large symptomatic renal cysts and is associated with high success rates and low complication rates in long‐term follow‐up . Also, some other methods have been reported using the retrograde ureteroscope to expand or fenestrate the renal cyst convex thin walls by holmium laser and make them communicate with the pelvis . In China, Shao Z Q et.…”
Section: Discussionmentioning
confidence: 99%
“…have reported to use a rollerball electrode to treat renal cyst by inspecting and cauterizing the inter cyst surface through a 26Fr percutaneous channel; this method has been shown to be a safe, minimally invasive, and effective technique for the management of large symptomatic renal cysts and is associated with high success rates and low complication rates in long‐term follow‐up . Also, some other methods have been reported using the retrograde ureteroscope to expand or fenestrate the renal cyst convex thin walls by holmium laser and make them communicate with the pelvis . In China, Shao Z Q et.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that ( 20 , 21 ) when treating endogenous cyst with flexible ureteroscope, the best incision position cannot be precisely determined; it was difficult to find the best laser rupture position for the cyst in the calyx and pelvis by ureteroscope; the incision cannot be found because of the thick cyst wall. Therefore, effective assessment of whether the flexible ureteroscope can handle specific endogenous cysts before surgery and how to effectively locate the cyst is a key factor for the success of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…13,18,19 The pathogenesis of simple renal cysts and parapelvic cysts is almost the same. 20 Therefore, in our study also, the 70-keV virtual monochromatic images were chose to perform quantitative measurements.…”
Section: Discussionmentioning
confidence: 99%